Aging of allochthonous organic carbon regulates bacterial production in unproductive boreal lakes - Berggren, Martin; Laudon, Hjalmar; Jansson, Mats (Limnology and Oceanography, 2009)
We calculated average aquatic dissolved organic carbon (DOC) age (the time span from soil discharge to observation) in water from the inlets and outlets of two unproductive Swedish lakes at different times during an annual cycle. Bacterial production (BP) and bacterial growth efficiency (BGE) determined during 7-d bioassays decreased with increasing average aquatic DOC age. Parallel to the declines in BP and BGE there was a rise in specific ultraviolet absorbance at the wavelength of 254 nm (SUVA(254)), which indicates that decreasing BP and BGE were connected to a shift to a more aromatic and recalcitrant DOC pool. The relationships between bacterial metabolism and DOC age were stronger after a Q(10) correction of the DOC age, showing that temperature affected rates of DOC quality changes over time and should be taken into account when relating lake bacterial growth to substrate aging in natural environments. We propose that hydrological variability in combination with lake size (water renewal time) have a large influence on pelagic BP in lakes with high input of terrigenous DOC.
Keywords: NORTHERN SWEDEN; BACTERIOPLANKTON PRODUCTION; GROWTH EFFICIENCY; HUMIC LAKE; MICROBIAL-DEGRADATION; COMMUNITY STRUCTURE; MATTER; ORTRASKET; EXPORT; PHYTOPLANKTON